PROSPECTS FOR THE USE OF POLYMER MATERIALS IN CAR REPAIR (Journal of Multidisciplinary Sciences and Innovations, 2025)
It is difficult to imagine the designs of modern vehicles without polymer materials. The use of these materials, along with streamlining the designs of technical means, reducing their mass, and increasing operational reliability, opens a wide way to reducing production costs and labor costs. The widespread use of polymer materials is due to their ability to directly replace precious metals and wood materials, often surpassing them.